Characterizing G-quadruplexes, a novel regulatory element, in Streptomyces bacteria - Colameco, Savannah (My University, 2018)
Less is known about the mechanisms that govern gene regulation in GC-rich bacteria than in the more AT-rich model organisms like Escherichia coli and Bacillus subtilis. G-quadruplexes (GQs) are stable structures that form in G-rich nucleic acid sequences, and have the potential to be important regulators of gene expression – particularly in GC-rich organisms. Streptomyces are extremely GC-rich bacteria with the capacity to produce a vast range of antibiotic compounds. There are still many gaps in our understanding of gene regulation in these bacteria, and yet GQ sequences have never been investigated for their regulatory potential in Streptomyces, even though they are known to play important roles in various eukaryotic systems. Here, we performed an in-depth in silico analysis of the S. venezuelae genome and found an abundance of GQ sequences in these genomes. We discovered that these sequences were enriched in putative regulatory regions and in antibiotic biosynthetic clusters. We followed up this in silico analysis with reporter assays that demonstrated that GQ sequences affected gene expression in Streptomyces. We also took steps towards elucidating the mechanism of action for an observed increase in reporter activity in the presence of the GQ sequence. Finally, we discovered two proteins, SVEN_2656 and SVEN_3866, with the potential to interact with GQ sequences and may function in preventing adverse effects of GQ structures. These results indicate that GQs have the potential to act as important regulators of gene expression in Streptomyces bacteria, and future work on these systems could lead to a broader understanding of gene regulation in all bacteria, and in Streptomyces specifically, could be employed to stimulate antibiotic production.